Posture and mobility of the upper body quadrant and pulmonary function in COPD: an exploratory study - Morais, Nuno (2018)
Background: There is limited evidence regarding interactions between pulmonary (dys)function, posture, and mobility of the upper body quadrant in patients with chronic obstructive pulmonary disease (COPD). Objectives: This exploratory study aimed to investigate whether postural alignment and mobility of the upper quadrant are related to changes in pulmonary function and compare such variables between patients with COPD and healthy individuals. Method: Fifteen patients with COPD (67.93±9.71yrs) and 15 healthy controls (66.80±7.47yrs) participated. Pulmonary function (FEV1, FVC) was assessed with spirometry. Alignment and mobility of the head, thoracic spine, and shoulder were assessed using digital photographs. Pectoralis minor muscle (PmM) length and thoracic excursion were assessed with a measuring tape. Groups were compared and linear regression analyses were used to assess potential relationships between postural and mobility variables and pulmonary function. Results: Patients with COPD were more likely to have a forward head position at maximal protraction (28.81±7.30o vs. 35.91±8.56o, p=0.02) and overall mobility of the head (21.81±10.42o vs. 13.40±7.84o, p=0.02) and a smaller range of shoulder flexion (136.71±11.91o vs. 149.08±11.58o, p=0.01) than controls. Patients’ non-dominant PmM length and maximal head protraction were predictors of FEV1 (r2adjusted=0.34). These variables, together with the upper thoracic spine at maximal flexion and thoracic kyphosis at maximal extension, were predictors of FVC (r2adjusted=0.68). Conclusion: Our findings suggest that impaired pulmonary function is associated with muscle length and mobility adaptations. Further studies are needed to understand the underlying mechanisms and clinical value of these relationships.